The association of pericardial fat with incident coronary heart disease: the Multi-Ethnic Study of Atherosclerosis (MESA)(1)(2)(3) - Ding, Jingzhong (American Society for Nutrition, 2009)
Background: Pericardial fat (ie, fat around the heart) may have a direct role in the atherosclerotic process in coronary arteries through local release of inflammation-related cytokines. Cross-sectional studies suggest that pericardial fat is positively associated with coronary artery disease independent of total body fat. Objective: We investigated whether pericardial fat predicts future coronary heart disease events. Design: We conducted a case-cohort study in 998 individuals, who were randomly selected from 6814 Multi-Ethnic Study of Atherosclerosis (MESA) participants and 147 MESA participants (26 from those 998 individuals) who developed incident coronary heart disease from 2000 to 2005. The volume of pericardial fat was determined from cardiac computed tomography at baseline. Results: The age range of the subjects was 45–84 y (42% men, 45% white, 10% Asian American, 22% African American, and 23% Hispanic). Pericardial fat was positively correlated with both body mass index (correlation coefficient = 0.45, P < 0.0001) and waist circumference (correlation coefficient = 0.57, P < 0.0001). In unadjusted analyses, pericardial fat (relative hazard per 1-SD increment: 1.33; 95% CI: 1.15, 1.54), but not body mass index (1.00; 0.84, 1.18), was associated with the risk of coronary heart disease. Waist circumference (1.14; 0.97, 1.34; P = 0.1) was marginally associated with the risk of coronary heart disease. The relation between pericardial fat and coronary heart disease remained significant after further adjustment for body mass index and other cardiovascular disease risk factors (1.26; 1.01, 1.59). The relation did not differ by sex. Conclusion: Pericardial fat predicts incident coronary heart disease independent of conventional risk factors, including body mass index.